An isometric normative database to facilitate restoration of function in knee-injured active young adults - J. Charteris (AOSIS, 1993)
Prohibitive costs technologically advanced dynamometers need not dissuade rehabilitationists from making useful assessments of musculo-skeletal performance in clinical settings. The use of simple strain-gauge measures of isometric torque is demonstrated using knee flexor-extensor capacities, dominance ratios, contralateral asymmetries and sexual dimorphism ratios. Functional restoration of knee-injured active young adults, using normative charts as a data base, is a cheap and feasible option.